LA GLOBALIZACIÓN Y LOS CÍRCULOS CONCÉNTRICOS DE INTEGRACIÓN EN EL NUEVO ORDENECONÓMICO MUNDIAL - Ugarte Vega Centeno, Máximo Alfredo (2011)
Not only Europe is making progress in creating a single market in its territory, it’s just another link in a major global trend towards grouping of countries with common commercial interests; the countries of Latin America are trying to spread their common interests within organizations to enable them to participate with greater weight in the world economy. A future of interdependent economic blocs is just around the corner.